English and Malay verb functions : a cross-linguistic study - Siti Afifah Hashim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study mainly examines grammatical signs that convey six verb function messages in English and Malay; Linguistic Trueness (Factuality), Immediacy, Control, Person, Focus Number and Purpose and how consistently these grammatical signs convey all the messages. This cross-linguistic study also seeks to discover if there are similarities and differences in the use of the grammatical signs and also to discover how much English and Malay rely on grammatical signs to convey all the six verb functions messages. Knowing how much the two languages rely on grammatical signs to communicate the various messages is essential in providing some hints or clues for the researcher to make an assumption as to whether or not the English and Malay are synthetic in nature. Using a meaning-based framework proposed by Reid (1991) and Govindasamy (2005), both advocates of the Columbia School of Linguistics, this study examines the verb features or grammatical signs in English and Malay from two different genres; academic and journalistic. Data was culled from 30 English academic articles (TESOL Quarterly), 30 English journalistic articles (The Economist), 30 Malay academic articles (Jurnal Pendidik/Asia Pacific Journal) and 30 Malay journalistic articles (Dewan Masyarakat). Results showed that the verb functions Factuality, Immediacy, Control, Person and Focus Number are supported by grammatical signs in English; English relies on grammatical signs to convey these messages. It was found that that these verb functions i.e. Factuality, Immediacy, Control, Person and Focus Number are supported partially in Malay; Malay does have grammatical signs to convey these messages but fewer compared to English. The verb function Purpose is supported by grammatical signs in Malay but not in English. There are grammatical signs that convey the Purpose message in Malay but no specific grammatical signs were found to convey such message in English. When there are no grammatical signs found to convey the message, it means that context is needed to help language users interpret the intended message. It was discovered that there are a few verb features that interfere the provision of the information on the six verb functions; To+V (English), Untuk+V (Malay), Modal+V (English, Malay), V+ing (English), V+en (English), V+ed (English), Syntagmatic Relation (English) and Others (English). It has to be noted that even though these verb features or grammatical signs do not convey the verb function messages, they do carry other meanings. The overall results also showed that both English and Malay do not qualify/do not meet the criteria to be regarded as synthetic languages. They are both analytical as much context is needed to communicate the verb function messages.